2010
DOI: 10.1159/000313425
|View full text |Cite
|
Sign up to set email alerts
|

Flying with Respiratory Disease

Abstract: Patients with respiratory diseases may be at risk during flight because at cruising altitude an important hypobaric hypoxia may occur. The only absolute contraindications to flying in these patients are pneumothorax, bronchogenic cyst and severe pulmonary hypertension. In order to evaluate the risks related to air travel in patients with respiratory diseases, an evaluation of their fitness to fly, including the hypoxia altitude simulation test, is required. The fitness to fly evaluation can identify patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 91 publications
0
26
0
Order By: Relevance
“…Consecutively, this decrease in ambient oxygen partial pressure translates into a considerable decrease in the oxygen saturation in the peripheral blood (85 and 91%, respectively) and mean arterial oxygen pressure (53 and 64 mm Hg, respectively), nota bene in healthy volunteers [48] . In healthy subjects, this decrease in oxygen saturation is well tolerated in most instances, whereas hypoxia during aircraft travel may induce discomfort and medical complications in patients with pulmonary diseases [49] . While our study on increased activity in IBD patients after exposure to hypoxia [45] indeed revealed a significant association between inflammation and hypoxia, there are currently no clinical studies available in the literature.…”
Section: Key Messagesmentioning
confidence: 99%
“…Consecutively, this decrease in ambient oxygen partial pressure translates into a considerable decrease in the oxygen saturation in the peripheral blood (85 and 91%, respectively) and mean arterial oxygen pressure (53 and 64 mm Hg, respectively), nota bene in healthy volunteers [48] . In healthy subjects, this decrease in oxygen saturation is well tolerated in most instances, whereas hypoxia during aircraft travel may induce discomfort and medical complications in patients with pulmonary diseases [49] . While our study on increased activity in IBD patients after exposure to hypoxia [45] indeed revealed a significant association between inflammation and hypoxia, there are currently no clinical studies available in the literature.…”
Section: Key Messagesmentioning
confidence: 99%
“…Because of this, the partial pressure of oxygen in inspired gas (PiO 2 ) decreases by 40 mm Hg as compared to sea level. These pressure changes are attained approximately 15 min following takeoff [6]. …”
Section: Discussionmentioning
confidence: 99%
“…The average increase in gas volume upon moving from the ground to 8,000 ft osl is approximately 30%. The reduction in atmospheric pressure that occurs during ascent can cause a dramatic increase in noncommunicating gas volume and consequently rupture of an underlying pulmonary cystic lesion leading to pneumothorax, and this is the likely mechanism in the index case also [6]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations